(untitled) (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2013)
This paper researches about the effect that the Spanish codes of best practices incorporate governance have produced on Spanish publicly held companies included in the Ibex 35 index. The results that have been found are:1. The effect caused by codes is poor; companies barely follow each individual recommendation proposed by codes.2. The effect caused by codes on the global corporate governance structure of the studied companies was to homogenize them; codes have played here some role,although the one played by the Olivencia code has been more important than theone played by the Aldama code.